Factors that affect cognitive and mental emotional development of children: a scoping review - Rini Sartika; Djauhar Ismail; Luluk Rosyida (Journal of Health Technology Assessment in Midwifery, 2021)
One of the factors that affect the quality of children is growth and development that takes place optimally. Cognitive and mental emotional development is very important for children's growth and development both for the present and the future. The purpose of this scoping review was to determine the factors that are related to the cognitive and mental emotional development of children. The method of this scoping review uses 4 databases (Pubmed, Wiley Online Library, Science Direct, and Springer Link), the search is limited to articles published in the last 10 years (2010-2020). The study was identified using the PRISMA flowchart, in conducting critical appraisal the researcher conducted an assessment using JBI tools. The findings of this scoping review are that factors that are associated with children's cognitive development are parental factors (maternal depressive and anxiety disorder) and child factors (child's condition at birth, stunting, and hemoglobin levels). Factors related to children's emotional mental development are parental factors (family socioeconomic, parenting styles, family mental health, parental education level, and parents' marital conflict), child factors (children's health conditions), and factors. other (regional characteristics). Of the factors associated with children's cognitive development, the most frequent factor emerged from the 10 articles reviewed. namely the factors of the parents maternal depressive and anxiety disorder and the factors of the child, namely the condition of the child at birth. Then, from the factors related to the mental emotional development of children, the parent factor in the form of family socioeconomic factors is the most frequent factor that appears from the 10 articles that have been reviewed.